A transient flow solution to describe fluid flow to horizontal fractures applied to frac‐packed wells. Issue 10 (18th August 2021) - Guo, Boyun; Fu, Chunkai; Liu, Ning
Abstract: This paper presents an analytical model to describe the transient fluid flow to a horizontal fracture in frac‐packed vertical wells. A physical model is first established where a horizontal frac‐packed fracture is located in the middle of a cylindrical reservoir. The pressure distribution in the fracture is then derived concerning time and the distance to the wellbore. The analytical model assumes a homogeneous and isotropic reservoir where Darcy's law applies to a single‐phase fluid flow, a radial fracture with a radius much greater than pay zone thickness, and a constant fracture width. For ease of application, a Type Curve Matching approach is introduced which features the matching of a defined dimensionless pressure between field pressure data and model data, and some exemplar curves are illustrated in this paper. The principle of applying curve matching here is to tune model parameters to match the measured pressure/rate data. Once the curves are matched, the model parameters, that is, fracture permeability, etc, are naturally obtained. The validity of the derived model is informed in two ways. The results show that the model will degenerate to the classic radial flow equation for practical values of certain model parameters and upon reasonable simplification. Model validity is further verified by applying the type curve matching technique using field data. This model can be used as a quick and reasonable method to analyze the transient pressure/rate test data to reveal fundamental fracture and reservoir properties for a frac‐packed horizontal fracture at shallow depths where the vertical formation stress is the least in situ stress. Abstract : The analytical model proposed here utilizes the transient pressure data in well testing to reveal the fundamental reservoir and fracture properties along the flow path of the fluid. An initial case study with field data shows a good match with the results from the analytical model using the Type curve matching technique proposed in this paper.